KARAKTERSTIK SERAPAN SUARA KOMPOSIT POLYESTER BERPENGUAT SERAT TAPIS KELAPA - Astika, I Made; Dwijana, I Gusti Komang (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2016)
The purpose of this study is to investigate of sound absorption of coconut filter fiber composites. The research material made with coconut filter fiber as reinforcement and matrix resin unsaturated polyester (UPRs) type Yukalac BQTN 157 with 1% hardener types MEKPO (Methyl Ethyl Ketone Peroxide) and fiber treatment by  0,5% KMnO4. Production methods is poltrusion and the variations of fiber volume fraction are 20, 25 and 30% and fiber length are 5, 10 and 15 mm. Testing of sound absorption frequency are 250, 500, 1000, 2000 and 4000 Hz. The results of research show that  the highest value of sound absorption coefficient is on  the composites with composition of 10 mm fiber length and 30% fiber volume fraction, that is 0.550828. The values are included in the class “Sound Absorption Coefficient Class D (Extremely absorbing)” with the range 0.40 – 0.60 based on ISO standard 11654:1997.